Design of Bi-and Tri-metal Oxide Photocatalysts via Gelatin-Directed Mesoporous Silica Hard Templating for Advanced Dye Degradation - Ulfa, Maria; Lestari, Suwiji (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2025)
This study aims to develop a photocatalyst combination of NiO, CuO and ZnO metal oxides modified with mesoporous silica gelatin (mSG) to overcome methylene blue (MB) dye waste through photodegradation process. The photocatalysts were synthesized using the hard template method with mSG as the matrix and tested for their performance towards MB degradation under ultraviolet light. Characterization results showed that the G-Ni-Cu-Zn photocatalyst has a larger surface area, better crystalline structure, nano particle size ( 26 nm), and band gap energy of 3.16 eV compared to G-Ni-Zn which has a very low surface area, larger particle morphology ( 0.46 μm), and band gap energy of 2.13 eV. Photodegradation tests showed a maximum degradation efficiency of 83.67% by G-Ni-Cu-Zn in 120 minutes, which is much higher than that of G-Ni-Zn. Copyright © 2025 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).